Genome Sequence of the Alcelaphine Gammaherpesvirus 1 Attenuated Laboratory Strain WC11 - Enßer, Armin (Genome Announcements, 2017)
The complete genome sequence of the alcelaphine gammaherpesvirus 1 (AIHV-1) attenuated laboratory strain WC11 was determined from purified virion DNA. The viral light DNA (L-DNA) genome of 127,215 bp is mostly conserved compared to the pathogenic strain C500; however, 3.3 kb is deleted in two regions, affecting 4 of 10 AIHV-1-specific open reading frames.
EVALuna2:35814